Variation in juvenile Chinook salmon (Oncorhynchus tshawytscha) transcription profiles among and within eight population crosses from British Columbia, Canada. Issue 8 (19th April 2019) - Toews, Shelby D.; Wellband, Kyle W.; Dixon, Brian; Heath, Daniel D.
Abstract: Phenotypic differences among populations within a species have been reported for a variety of traits, ranging from life history to physiology to gene transcription. Population‐level phenotypic variation has been attributed to genetic differences resulting from genetic drift and/or local adaptation as well as environmental differences resulting from plasticity. We studied population‐ and family‐level variation in gene transcription for 22 fitness‐related genes, comprising immune, growth, metabolic, and stress processes in Chinook salmon ( Oncorhynchus tshawytscha ). We created hybrid Chinook salmon families from eight populations and treated them with an immune stimulus, a handling stress challenge, and held some as a no‐treatment control group. Population effects, sire effects, and narrow‐sense heritability ( h 2 ) were calculated for each candidate gene within each treatment group. We expected population to have a significant effect on gene transcription for many of our genes; however, we found a population effect for transcription at only one immune gene at rest. The limited number of significant population effects on gene transcription, combined with significant additive genetic variance within each population does not support the expectation of past strong selection pressures acting on heritable transcription profiles among populations. Instead, our results indicate that Chinook salmon likely adapt to their local environment through transcriptional plasticity rather than fixed differences. The expectation for fixed population‐level differences in gene transcription at fitness‐related genes, reflecting accepted models of local adaptation is high; however, comparisons among multiple populations using half‐sibling breeding designs are rare. Our work fills an important gap in our growing understanding of the process of among and within‐population divergence.